(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: New-born Brachial Plexus Palsy (NBPP) is birth injury resulting from traction to the brachial plexus at birth. It is an injury to two or more cervical or thoracic nerve roots. It has been reported to be one of the most common birth injuries of the new-born. Persistent presentation of children with NBPP in Nigeria paediatric practice necessitates the need to examine prevalence, patterns and possible predisposing factors. This study therefore investigated retrospectively, profiles of children who presented with NBPP over a ten year period and were managed at the Physiotherapy department of the University College Hospital, Ibadan Nigeria. A retrospective cross-sectional survey, in which files of children with NBPP located from the database of the Physiotherapy department were retrieved in order to assess infant and maternal information. One hundred and seventy children, 93 (54.7%) males and 77 (45.3%) females were studied. Their mean birth weight was 4.21±0.54 kg, 99 (58.2%) were delivered in private (non-government) hospitals, majority 163 (95.9%) presented with Erb’s Palsy. Mothers, 54 (31.8%) were mostly primiparous and a seemingly persistent elevation in two-yearly incidence of NBPP was observed. Improved healthcare policy in child delivery is encouraged in non-government hospitals in Nigeria to provide preventive measures toward incidence of NBPP. Documentation of physiotherapy management of children with NBPP should include outcomes from admission through to discharge